Gadobutrol: Development and Validation of a Method for Determining the Content of Elemental Impurities Using Inductively Coupled Plasma Mass Spectrometry - V. M. Shchukin; Yu. N. Shvetsova; V. A. Lapina; N. E. Kuz'mina (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION . Gadobutrol is a macrocyclic gadolinium-based contrast agent used in diagnostic magnetic resonance imaging (MRI). In accordance with pharmacopeial requirements, the determination of elemental impurities in this substance is mandatory. The high concentration of gadolinium in the matrix, relative to the regulated permissible limits of target impurities, necessitates specialized methodological approaches for elemental analysis. AIM . To develop and validate a method for determining elemental impurities in gadobutrol using inductively coupled plasma mass spectrometry. MATERIALS AND METHODS . The method was developed using model mixtures containing standard solutions of the elements analyzed (Cd, Pb, As, Hg, Co, V, Ni, Tl, Au, Pd, Ir, Os, Rh, Ru, Se, Ag, Pt, Li, Sb, Ba, Mo, Cu, Sn, and Cr). The oxidant mixtures and digestion methods were varied. Validation samples were prepared using a 200-fold dilution of gadobutrol (blank solution), to which varying amounts of standard solutions of the elements were added. The elemental content was determined using an Agilent 7900 inductively coupled plasma mass spectrometer. When selecting the measured Pt and Se isotopes, isobaric interferences arising from high concentrations of Gd in the matrix (198Pt and 82Se) were taken into account. To suppress polyatomic interference, a collision cell operated in helium mode was used. The following stabilizers were used to bind OsO4: aqueous solutions of sodium sulfite (7.5 g/L), potassium bisulfite (7.5 g/L), and thiourea (1 g/L). RESULTS . It was found that the use of H2O2 does not result in a significant improvement in element recovery. The optimal sample preparation is microwave digestion in a 4:1 mixture of nitric and hydrochloric acids at 150 °C. Thiourea solution is the most effective stabilizing agent for obtaining accurate Os determination results. The assessed validation parameters (linearity, accuracy, repeatability, within-laboratory precision, and specificity) meet pharmacopeial acceptance criteria. The working range of the method enables the determination of all regulated elements at the levels specified by pharmacopeial requirements. CONCLUSIONS . The developed and validated method is recommended for implementation in the assessment of risks associated with the potential adverse effects of elemental impurities introduced into the human body upon administration of the Gadobutrol medicinal product.